Roles of Macrophage Migration Inhibitory Factor in Dengue Pathogenesis: From Pathogenic Factor to Therapeutic Target - Lai, Yen-Chung (Microorganisms, 2020)
Dengue virus (DENV) infection is the most prevalent mosquito-borne viral infection and can lead to severe dengue hemorrhagic fever (DHF) and even life-threatening dengue shock syndrome (DSS). Although the cytokine storm has been revealed as a critical factor in dengue disease, the limited understanding of dengue immunopathogenesis hinders the development of effective treatments. Macrophage migration inhibitory factor (MIF) is a pleiotropic proinflammatory cytokine that mediates diverse immune responses, and the serum level of MIF positively correlates with disease severity in patients with dengue. MIF is involved in DENV replication and many pathological changes, such as vascular leakage, during DENV infection. In this paper, the pathogenic roles of MIF and the regulation of MIF secretion during DENV infection are reviewed. Furthermore, whether MIF is a potential therapeutic target against DENV infection is also discussed.